POST SURGICAL COMPLICATIONS FACED BY STUDENTS DURING LARGE ANIMAL SURGERY - A. A. Farooq; C.S. Hayat (Journal of Animal and Plant Sciences, 2007)
One hundred and fifty three surgical complications were recorded in retrospective study of operations carried out in the students large animal surgical laboratories in the department of clinical sciences, Gomal College of Veterinary Sciences, Gomal University D.I. Khan, Pakistan during the years 2003 to 2006. Wound infection (22.5%), wound dehiscence (20 %), hemorrhage (15%) and septicemia (15%) were the commonest complications observed. Other complications included, slipped ligature, intestinal obstruction, edema, myasis and death. Castration, opening of gutteral pouch, entrotomy and dehorning resulted in higher number of complications. Interviews from students conducted through questionnaires revealed that the animals with poor nutritional and health status, poor use of surgical instruments and septic surgical procedures were some of the factors that led to high incidence of complications. Management of complications entailed the use of systemic antibiotic treatment of surgical site as an open wound. Recommendations are made to avert occurrence of post surgical complications during the surgical practices adapted by students in large animal surgery.
Keywords: Surgical complications; student practical; donkey; goa